Aging studies of biodiesel and HVO and their testing as neat fuel and blends for exhaust emissions in heavy-duty engines and passenger cars. (1st August 2015) - Singer, A.; Schröder, O.; Pabst, C.; Munack, A.; Bünger, J.; Ruck, W.; Krahl, J.
Abstract: An increasing use of renewable fuels in the transport sector reduces the dependency on fossil oil and lowers the emission of greenhouse gases. This is a prime political and economic goal in Europe and also in many other parts of the world. In the diesel fuel sector, especially fatty acid methylesters are introduced as renewable fuels. This so-called biodiesel is mostly added to common diesel fuel in amounts of up to 20%. A further increase of the biodiesel content in the fuel is prevented by the increase of engine oil dilution by biodiesel in vehicles equipped with a diesel particulate filter (DPF). Biodiesel in the engine oil can lead to oil sludge formation. Emissions on one hand as well as oil sludge formation on other hand are important issues in fuel research and for implementation of new fuels. Besides biodiesel, hydrotreated vegetable oil (HVO) was recently introduced into the market exemplified at a new fuel called Diesel regenerativ . Hydrogenation of vegetable oil produces a fuel free of sulfur and aromatics with a high cetane number. HVO and biodiesel were tested in aging studies with base oil, whereby biodiesel is lubricant itself. These laboratory studies were carried out in order to simulate the formation of oil sludge in the engine. Diesel regenerativ is a fuel consisting of HVO with an admixture of 7% biodiesel. The biodiesel has the tendency to coagulate. This can lead to oil sludge formation if the fuel enters the engine oil. The base oil examinations showed a faster oil sludge formation with biodiesel than with HVO. In addition to these investigations the effects of HVO on the regulated and non-regulated emissions had also been tested extensively on heavy-duty engines and in a passenger car fleet test. The emissions of HVO and biodiesel were compared using a Euro III and a Euro IV heavy-duty engine with and without exhaust gas aftertreatment system. Furthermore, three passenger cars (Euro 3, 5 and 6) were examined in a fleet test for regulated and non-regulated emissions. The results showed that all heavy-duty engine emissions were lowered with the usage of HVO, compared with diesel fuel. In comparison with biodiesel, HVO also shows lower NOX emissions. This trend could not be confirmed using the passenger cars. In this investigation nitrogen oxide emissions increased between 5% and 14% versus diesel fuel. The increase was independent of the exhaust treatment.